Chronic infarct size after spontaneous coronary artery dissection: implications for pathophysiology and clinical management. (3rd January 2020) - Al-Hussaini, Abtehale; Abdelaty, Ahmed M S E K; Gulsin, Gaurav S; Arnold, Jayanth R; Garcia-Guimaraes, Marcos; Premawardhana, Diluka; Budgeon, Charley; Wood, Alice; Natarajan, Nalin; Mangion, Kenneth; Rakhit, Roby; Hoole, Stephen P; et al.
Abstract: Aims: To report the extent and distribution of myocardial injury and its impact on left ventricular systolic function with cardiac magnetic resonance imaging (CMR) following spontaneous coronary artery dissection (SCAD) and to investigate predictors of myocardial injury. Methods and results: One hundred and fifty-eight angiographically confirmed SCAD-survivors (98% female) were phenotyped by CMR and compared in a case–control study with 59 (97% female) healthy controls (44.5 ± 8.4 vs. 45.0 ± 9.1 years). Spontaneous coronary artery dissection presentation was with non-ST-elevation myocardial infarction in 95 (60.3%), ST-elevation myocardial infarction (STEMI) in 52 (32.7%), and cardiac arrest in 11 (6.9%). Left ventricular function in SCAD-survivors was generally well preserved with small reductions in ejection fraction (57 ± 7.2% vs. 60 ± 4.9%, P < 0.01) and increases in left ventricular dimensions (end-diastolic volume: 85 ± 14 mL/m 2 vs. 80 ± 11 mL/m 2, P < 0.05; end-systolic volume: 37 ± 11 mL/m 2 vs. 32 ± 7 mL/m 2, P <0.01) compared to healthy controls. Infarcts were small with few large infarcts (median 4.06%; range 0–30.9%) and 39% having no detectable late gadolinium enhancement (LGE). Female SCAD patients presenting with STEMI had similar sized infarcts to female Type-1 STEMI patients age <75 years. Multivariate modelling demonstrated STEMI at presentation, initial TIMI 0/1 flow, multivessel SCAD, and a Beighton score >4 were associated with larger infarcts [>10% left ventricular (LV) mass]. Conclusion: The majority of patients presenting with SCAD have no or small infarctions and preserved ejection fraction. Patients presenting with STEMI, TIMI 0/1 flow, multivessel SCAD and those with features of connective tissue disorders are more likely to have larger infarcts.